Enhancing Practical AI Competency with YOLO 2D Detector Object Localization Technology - Nova Eka Budiyanta; Hanugra Aulia Sidharta; Stefani Prima Dias Kristiana; Diah Risqiwati (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2025)
Object locatization is one of important aspect of computer vision, which refers to a system's ability to detect and determine the position of objects within an image. However, general audience practical understanding of object localization is remains limited. To address this issue as a community service team, and organized a workshop focused on YOLO (You Only Look Once)-based object localization. This workshop was conducted free of charge online via the Google Colab platform. The event was successfully carried out and received positive feedback from the participants. This workshop are providing a real studycase through brain tumor detection from image-based approaches, aiming to provide an in-depth experience in object localization while also offering the latest updates on artificial intellegent technology trends based on digital image processing. Based on evaluation results indicated that the majority of participants, who previously had no experience in object detection, were able to understand the fundamental concepts of object localization and apply them directly using the cloud platform. This workshop demonstrates that cloud-based learning approaches utilizing Google Colab and Roboflow are highly effective in bridging the gap between theory and practice in object localization.